Where and What Kind-A Better Understanding of Local and Landscape Features in Planning the Urban Flower Meadows for Supporting Bee Communities - Kostro-Ambroziak, Agata; Sobieraj-Betlińska, Anna; Szefer, Piotr; Suprunowicz, Urszula; Ulaszewski, Bartosz; Pliszko, Artur; Burzyńska, Justyna; Charubin, Beata; Wróbel, Karolina; Mierzyńska, Karolina; Kozikowski, Daniel; Jermakowicz, Edyta (Ecology and evolution, 2025)
Cities are growing ecosystems in the modern world. Due to their heterogeneity, urban areas have multifaceted influences on organisms, including bees. However, in many specific city greenspace designs and management implementations, our understanding of their functionality remains limited. This is also true for urban flower meadows (UFMs). We extensively examined UFMs in three large cities to answer the following question: What features of UFMs and their surroundings (urban matrix) are the most important in supporting bees in cities? Our multifaceted approach revealed that the mosaics of habitats surrounding UFMs are at least as necessary to support bees as the local features of UFMs. An abundance of bees responded positively to the number of flowering units and the blue and yellow colors of flowers, and increased cover of industrial areas, green urban areas, and pastures in a 100-m buffer. Increasing the cover of the continuous urban fabric in all buffer zones (100, 300, and 500 m) positively affected bee species richness and abundance. Due to the lack of design guidelines for urban flower meadows, our results are helpful for the further planning of UFMs to optimize bee-friendly areas in urban landscapes.
Keywords: urban greenspaces; urban ecology; urban ecosystems; pollinators; designed landscapes